High-frequency ventilation for non-invasive respiratory support of neonates. Issue 3 (June 2016) - Yoder, Bradley A.; Albertine, K.H.; Null, D.M.
Summary: Non-invasive respiratory support is increasingly used in lieu of intubated ventilator support for the management of neonatal respiratory failure, particularly in very low birth weight infants at risk for bronchopulmonary dysplasia. The optimal approach and mode for non-invasive support remains uncertain. This article reviews the application of high-frequency ventilation for non-invasive respiratory support in neonates, including basic science studies on mechanics of gas exchange, animal model investigations, and a review of current clinical use in human neonates.